An investigation of Papuan English Teachers' Emotional Management during Teaching - Romrome, Abel Yohanis; Mbato, Concilianus Laos (Language Circle: Journal of Language and Literature, 2022)
Emotional management is one crucial skill that teachers should acquire. In this case, the teachers should be able to regulate their emotions to succeed in the teaching process. This study aimed to investigate how Papuan English teachers manage their emotions during teaching based on two research questions: 1. In which situation do Papuan English teachers experience positive and negative emotions? 2. To what extent can Papuan English teachers manage their emotions during teaching? The four participants who contributed to this study were experienced English teachers from two Junior High Schools in Timika, Papua, Indonesia. In this study, the researchers employed a qualitative method, specifically a descriptive case study. In collecting the data, the researchers used two types of instruments namely open-ended questions and semi-structured interviews. Meanwhile, the researchers used the thematic analysis method to analyze the data. Based on the findings, the positive emotions consisted of four elements such as happiness, motivating, confidence and pride. The negative emotions also encompassed four elements: anger, stress, sadness, and anxiety. In addition, the findings suggested that most participants had regulated their emotions properly and appropriately by employing several strategies such as avoiding harsh words during anger, self-relaxing, self-talking, and reflection. They also treated the students with care and love in building teacher-students' relationships (professional empathy).